Lower limb maximal dynamic strength and agility determinants in elite basketball players - Chaouachi, A.; Brughelli, M.; Chamari, K.; Levin, G. T.; Abdelkrim, N. B.; Laurencelle, L.; Castagna, C. (The Journal of Strength and Conditioning Research, 2009)
The aims of this study were to examine the relationship between squat 1 repetition maximum (1RM) and basketball-relevant tests and the variables that influence agility (T-test) in elite male professional basketball players (n = 14, age 23.3 ± 2.7 years, height 195.6 ± 8.3 cm, body mass 94.2 ± 10.2 kg). T-test performance was significantly related to body mass (r = 0.58, p = 0.03) and to percentage of body fat (r = 0.80, p < 0.001). A significant negative correlation was observed between t-test and 5-jump test performance (r = -0.61, p = 0.02). Squat 1RM was significantly related to 5-, 10-, and 30-m sprint times. Stepwise correlation analysis showed percentage of body fat was the best single predictor factor (p < 0.05) of agility. Squat 1RM performance was the best single predictor of 5-m and 10-m sprint times (p < 0.05). In light of the present study's findings, agility should be regarded as a per se physiological ability for elite basketball players. Consequently, basketball-specific agility drills should be stressed in elite basketball training. Given the association between squat 1RM performance and short sprint times, squat exercises should be a major component of basketball conditioning